Preliminary evaluation of an underutilized Red Sitaphal (Annona squamosa L.) peel for its phytochemical composition and in-vitro antioxidant activity - Banerjee, Adrita; AC, Lokesh; KN, Hanumantharaju; M, Rajadurai (Journal of Neonatal Surgery, 2025)
Background Red Sitaphal or Custard Apple is an underutilized minor cultivar of the common Annona squamosa fruit from Annonaceae family. This red fruit although produced in quite a large number, is neglected in commercial usage and processing sectors in India. It is important to explore the valorization potential of this fruit and its different parts like peels, seeds etc. to increase its consumption and reduce post-harvest losses. This study characterizes the phytochemical profile and antioxidant capacity of Red Sitaphal (Annona squamosa L.) peels, an underutilized agricultural by-product. Methods Through comparative analysis between different peel extracts, we identified significant concentrations of phenols and flavonoids, found in ethanolic extract. DPPH radical scavenging assay revealed a superior antioxidant activity with ethanol extract as compared to other extracts. Results Phytochemical screening confirmed the presence of alkaloids, polyphenols, and tannins, with ethanol preferentially extracting polar antioxidants while the non-polar solvents recovered terpenoids. Quantitatively, TPC and TFC were found to be 206.36±6.08 mg gallic acid/g & 67.74±2.51mg quercetin/g, respectively which was corroborated by the fairly moderate DPPH radical scavenging activity shown in the peel extracts. Conclusion These findings report a first comprehensive phytochemical screening for Red Sitaphal and establish their peel by-product as a source of natural antioxidants, suggesting their potential valorization in nutraceutical applications and sustainable waste reduction strategies. The distinct phytochemical profile compared to common green varieties highlights the need for cultivar-specific utilization approaches.